Exploring Nursing Undergraduates' Experiences with a Redesigned Blended Learning Course: A Descriptive Qualitative Study - Lu Wang; Bizhen Liao; Huanhuan Yang; Chunju Yang (Wiley, 2023)
Abstract Aim To explore the experience of nursing undergraduates with a blended course, that was redesigned using the Community of Inquiry framework. Design The Obstetrics and Gynaecology Nursing Course was redesigned using blended learning pedagogy, which starts from the creation of teaching presence, plays the intermediary role of social presence and aims at realizing cognitive presence. Methods After the course completion, we conducted a qualitative descriptive study and collected data using focus group interviews and field notes. Results The findings comprised three main themes including role promotion, passive and selective learning and recommendations. Teachers and peers reportedly played the supervisors, facilitators and coordinators in learning promotion. Some students experienced difficulties in adapting to the blended learning environment due to passive learning habits, character flaws and academic pressure. However, a majority of them supported the application of the model.